SOCIAL COMMUNICATION OF FARMERS IN ESTABLISHING FOOD SECURITY RECOVERY - Rully Khairul Anwar; Edwin Rizal; Elnovani Lusiana (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2020)
This study aimed to gain an overview of farmers' community in rural areas about a social communication model among them who have cultivated farmland from generation to generation. The qualitative and descriptive study in a village in Garut found that there were patterns of traditional communication maintained by the majority of farmers as well as open communication patterns with absorbs the modernization of development. With social communication pattern, it is clear that there are efforts to strengthen the resilience of rural communities which are sufficient dynamic to reduce the imbalance between rural and urban areas, reduce the level of dependence of the city, increase the income of farmers, and empowerment of farmers and poor communities in rural areas.